Eksistensi Lubuk Larangan Untuk Meningkatkan Pendapatan Ekonomi Masyarakat - Aisyah Aminda; Nuriza Dora (LPPM Politeknik Pratama, 2024)
Local wisdom is explicit knowledge that emerges from a period long term that has evolved together with society and its environmentlocal systems that have been experienced together. This research will discuss about local wisdom, namely the role of lubuk arangan in improving the economy society from the perspective of Islamic economic law. As a result of this research that the people in Gunung Tua Julu Village have the habit of opening pitsprohibitions on every Eid or religious holidays. Income from the bottom of the forbidden Part of it will be used for the Parmompang village treasury as one of them Parmompang village program to increase community economic income. By In simple terms, environmental management is the management of natural resources related to how to manage natural resources and methods society interacts with its environment by integrating planning, air management and conservation in the form of Lubuk Larangan. With management properly then Lubuk Larangan runs well and smoothly with results the maximum. The aim of the research is to find out what form of hole management takes prohibitions as a form of local wisdom in the Batang Jujuhan River, Bungo Regency. Qualitative descriptive method, namely to provide an overview and explanation factual and accurate regarding the facts and symptoms existing at the research location, Experiments, namely conducting surveys, collecting data and direct observations in field using questionnaire data or direct interviews with respondents.Meanwhile, secondary data includes an inventory of social, economic, environmental and environmental conditions.The results of the research state that there are forms of local wisdom of the community Parmompang Village, in an effort to manage lubuk ban, lubuk ban Parmompang Village consists of plan the formation of a prohibited hole through deliberation in an effort saving the river water environment, establishing rules and sanctions for forbidden lubuk and the rules alone, there are no sanctions for the forbidden lubuk,The people of Parmompang Village have the belief that those who take fish in the forbidden lubuk will dies,can change people's behavior towards a more positive aspect ecological and social, such as: Using environmentally friendly harvesting tools such as lukah,nets, nets etc., Prohibiting fishing along the prohibited pits, Maintaining and use the bottom as a breeding ground for fish,culture of the people in the forbidden area.